STRUCTURAL VIOLENCE AGAINST WOMEN IN KHYBER PAKHTUNKHWA: A CASE STUDY OF BUNER - Muhammad Rasheed; Chusnul Mar’iyah (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the pervasive issue of structural violence against women in the district Buner, Khyber Pakhtunkhwa, Pakistan. Drawing upon a comprehensive analysis of existing literature, questionnaires, and socio-economic data, this research sheds light on the intricate web of systemic factors contributing to the subjugation and marginalization of women in the area. With a primary objective of uncovering the forms, causes, and impacts of such violence, the study centers on four key variables: women’s deprivation of education, their restricted rights to inheritance, forced marriages, and their limited political participation. Employing a quantitative approach supplemented by a case study design, data were collected from a sample of 382 respondents across all six tehsils of District Buner. Additionally, secondary data were utilized to enrich the literature review and complement various sections of the study. From entrenched patriarchal norms and discriminatory legal frameworks to limited access to education and economic opportunities, the findings underscore the multifaceted nature of structural violence experienced by women in Buner. Furthermore, the study explores the implications of such violence on women’s well-being, autonomy, and socio-economic advancement, highlighting the urgent need for targeted interventions and policy reforms to address these systemic injustices. By situating the discussion within the context of Khyber Pakhtunkhwa and providing a comprehensive examination of the specific challenges faced by women in Buner, this research contributes to a deeper understanding of gender inequality and the mechanisms through which it is perpetuated in the region.